Postattenuation neurologic signs after surgical attenuation of congenital portosystemic shunts in dogs: A review. Issue 1 (29th September 2021) - Mullins, Ronan A.; Escribano Carrera, Antía; Anderson, Davina M.; Billet, Jean‐Philippe; Brissot, Herve; Broome, Cameron; de Rooster, Hilde; Kirby, Barbara M.; Pratschke, Kathryn M.; Tivers, Michael S.; White, Robert N.; Yool, Donald A.; et al.
Abstract: The development of postattenuation neurologic signs ( PANS ) is a poorly understood and potentially devastating complication after surgical attenuation of congenital portosystemic shunts in dogs. Postattenuation neurologic signs include seizures but also more subtle neurologic signs such as depression, behavioral changes, tremors, and twitching. They most commonly occur within 7 days postoperatively and are typically unrelated to hyperammonemia, hypoglycemia, or electrolyte disturbances. This narrative review summarizes the findings of 50 publications from 1988‐2020 that report occurrence of PANS . While most published reports included only dogs affected by postattenuation seizures ( PAS ), others included dogs with any form of PANS . Overall, PANS (including PAS ) affected 1.6%‐27.3% of dogs, whereas incidence of PAS ranged from 0%‐18.2%. The etiology of PANS remains unknown; however, several theories have been proposed. Risk factors include preoperative hepatic encephalopathy, increasing age, and possibly certain breeds and extrahepatic shunt morphology. There is increasing evidence that prophylactic antiepileptic drugs do not prevent PANS . Treatment is centered around controlling neurologic signs with antiepileptic drugs and providing supportive intensive care. The 30‐day survival rate in studies that included a minimum of four dogs affected by PANS was 0%‐100% (median, 50.0%) and 0%‐75.0% (median, 37.5%) for those with PAS . Mortality associated with PANS was typically related to occurrence of generalized seizure activity. Prognostic factors positively associated with short‐term survival included having a history of preoperative seizures and development of focal seizures only. If affected dogs survived to discharge, survival for several years was possible, and the majority of neurologic signs manifested as part of the phenomenon of PANS appeared to resolve.